Pengaruh Persistensi Laba Dan Kualitas Akrual Terhadap Earnings Response Coefficient Pada Perusahaan Manufaktur Dan Keuangan Yang Terdaftar Di Bei Tahun 2016-2018 - Brigita Ahabba; Nurzi Sebrina (Jurnal Eksplorasi Akuntansi, 2020)
This study aims to examine the effect of earnings persistence and accrual quality on earnings response coefficient. The sample used was manufacturing and financial sector companies listed on the Stock Exchange in 2016-2018 with a sampling method that was purposive sampling, so sample was obtaines is 92 manufacturing companies and 61 financial companies. The results of this study are first, earnings persistence has a negative and not significant effect on ERC in the manufacturing sector, while a significant positive effect on ERC in the financial company sector, so these variables can determine the level of ERC. Second, accrual quality has a positive and insignificant effect on ERC in the two corporate sectors.